Analisis Pengaruh Locus of Control, Stress Kerja, Beban Kerja terhadap Kinerja Karyawan PDAM Tirtanadi Cabang Tuasan Medan - Harmen, Hilma; Indriani, Riza (Fakultas Ekonomi Universitas Kadiri, 2024)
This study analyzes the effect of Locus of Control, Work Stress, Workload on Employee Performance of PDAM Tirtanadi Tuasan Medan Branch. The sample consists of 80 people who are permanent employees of PDAM Tirtanadi Branch Tuasan Medan with the sample technique using total sampling. Data collection through distributing questionnaires, with the Partial Least Square (PLS) data analysis method. The results of this research show that Locus of Control has a positive effect on employee performance. Workload has a positive effect on employee performance and Workload has a positive effect on employee performance. PDAM Tirtanadi Branch of Tuasan Medan is then given some suggestions in this article.